Organs at risk in the brain and their dose-constraints in adults and in children: A radiation oncologist's guide for delineation in everyday practice. Issue 2 (February 2015) - Scoccianti, Silvia; Detti, Beatrice; Gadda, Davide; Greto, Daniela; Furfaro, Ilaria; Meacci, Fiammetta; Simontacchi, Gabriele; Di Brina, Lucia; Bonomo, Pierluigi; Giacomelli, Irene; Meattini, Icro; Mangoni, Monica; et al.
Abstract Purpose Accurate organs at risk definition is essential for radiation treatment of brain tumors. The aim of this study is to provide a stepwise and simplified contouring guide to delineate the OARs in the brain as it would be done in the everyday practice of planning radiotherapy for brain cancer treatment. Methods Anatomical descriptions and neuroimaging atlases of the brain were studied. The dosimetric constraints used in literature were reviewed. Results A Computed Tomography and Magnetic Resonance Imaging based detailed atlas was developed jointly by radiation oncologists, a neuroradiologist and a neurosurgeon. For each organ brief anatomical notion, main radiological reference points and useful considerations are provided. Recommended dose-constraints both for adult and pediatric patients were also provided. Conclusions This report provides guidelines for OARs delineation and their dose-constraints for the treatment planning of patients with brain tumors.